2012
DOI: 10.1007/s12040-012-0184-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic features of winter precipitation and its variability over northwest India

Abstract: Northwestern parts of India receive considerable amount of precipitation during the winter months of December-March. Although, it is only about 15% of the annual precipitation, the precipitation is very important for rabi crops and to maintain the glaciers extend in the Himalaya, which melt and supply water to the rivers during other seasons. The precipitation is mainly associated with the sequence of synoptic systems known as 'western disturbances'. The precipitation has considerable spatial and temporal vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 11 publications
3
44
0
Order By: Relevance
“…The weakened Indian monsoon, strengthening El Niño, and westerlies, combined with the huge topographic landform, exert climatic controls on the distribution of existing glaciers along all Himalayan regions and reduce precipitation there. Archer and Fowler (2004) indicated that the western Hindu Kush and Karakoram are largely exposed to the arrival of westerly midlatitude perturbations bringing precipitation during winter and early spring, whereas the eastern Himalayas is dominated by summer monsoon precipitation (Syed et al, 2006;Yadav et al, 2012). Their results are similar to those of this study.…”
Section: Mass Change Of Glaciers In Himalayan Regionsupporting
confidence: 85%
“…The weakened Indian monsoon, strengthening El Niño, and westerlies, combined with the huge topographic landform, exert climatic controls on the distribution of existing glaciers along all Himalayan regions and reduce precipitation there. Archer and Fowler (2004) indicated that the western Hindu Kush and Karakoram are largely exposed to the arrival of westerly midlatitude perturbations bringing precipitation during winter and early spring, whereas the eastern Himalayas is dominated by summer monsoon precipitation (Syed et al, 2006;Yadav et al, 2012). Their results are similar to those of this study.…”
Section: Mass Change Of Glaciers In Himalayan Regionsupporting
confidence: 85%
“…This area is characterized by a variety of meteoclimatic regimes and by the interaction of local and large-scale circulation systems, resulting in a large variability of the spatial distribution of observed precipitation trends (e.g., Solomon et al 2007). Two main sub-regions, exposed to the influence of different circulation patterns, can be distinguished in the HKKH area: the western Hindu-Kush Karakoram (HKK) is largely exposed to the arrival of westerly midlatitude perturbations bringing precipitation during winter and early spring, while the eastern Himalaya is dominated by summer monsoon precipitation (Archer and Fowler 2004;Syed et al 2006;Yadav et al 2012). These different circulation patterns also influence glacier dynamics and, as a consequence, the hydrological regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Winter precipitation in the WHR occurs under the influence of extratropical systems known as western disturbances (WDs) (Dimri and Dash, 2012;Yadav et al, 2012). These are the extratropical upper air troughs or cyclonic circulations (CCs) in midlatitude westerlies that move west to east across the Himalayan region Das 2002;Lang and Barros, 2004;Puranik and Karekar, 2009).…”
Section: Introductionmentioning
confidence: 99%